PENGARUH KUALITAS PELAYANAN, VARIASI MENU, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN - Kamanda Tri Gumelar; Handoyo Djoko Waluyo; Sri Suryoko (Jurnal Ilmu Administrasi Bisnis, 2016)
Resto Sambal Van Java is a middle class restaurant with the concept of Netherlands building and Javanese cuisine. The location of restaurant is very strategic, being in the crowded area of education in Tembalang territory, Semarang. This restaurant has had its own place in the hearts of loyal customers. However, the advantages offered by this restaurant is not optimal considered. There are some complaints still submitted by consumers, among others, the parking area facilities, hygiene, the size of meal, employees neatness and empathy, and other services are less than satisfactory for consumers. It will obviously be able to influence purchasing decisions. The aims of this study was to determine the influence of service quality, menu variation, and price on customers'decision to buy in Resto Van Java Sambal Tembalang, Semarang. The type of this research was explanatory research. Population in this research were the customers of Resto Sambal Van Java and the number of samples were 100 respondents. The sampling technique in this study was using a non-probability sampling with accidental and purposive sampling technique. The analytical method used was cross tabulation, correlation, determination, simple linear regression, multiple, t test and F test with SPSS version 20. Based on the survey results revealed that the service quality, menu variation, and prices have a significant effect on customers'decisions to bought here, either partially or simultaneously. Independent variables that have the biggest influence on purchasing decisions was the variable of price. The advice that can be given is to do the rearrangement in the parking area or by giving extra money to the parker in order to work more presentable, providing training period sufficient to new employees, improve hygiene (The food, and the restroom), keep the neatness of employees, job evaluation on a regular basis, increase the menu variations with maintaining the mainstay menu, presenting food portions and flavor consistently, always maintain the availability and selectthe fresh materials, sale prices with certain conditions, as well as improving the overall service of other services that consumers find it appropriate to make a purchase decision, repurchase, and they can recommend this place to other people.